Borrelia burgdorferi BBK32 Inhibits the Classical Pathway by Blocking Activation of the C1 Complement Complex - Garcia, Brandon L.; Zhi, H.; Wager, B.; Hook, M.; Skare, J. T. (My University, 2016)
Pathogens that traffic in blood, lymphatics, or interstitial fluids must adopt strategies to evade innate immune defenses, notably the complement system. Through recruitment of host regulators of complement to their surface, many pathogens are able to escape complement-mediated attack. The Lyme disease spirochete, Borrelia burgdorferi, produces a number of surface proteins that bind to factor H related molecules, which function as the dominant negative regulator of the alternative pathway of complement. Relatively less is known about how B. burgdorferi evades the classical pathway of complement despite the observation that some sensu lato strains are sensitive to classical pathway activation. Here we report that the borrelial lipoprotein BBK32 potently and specifically inhibits the classical pathway by binding with high affinity to the initiating C1 complex of complement. In addition, B. burgdorferi cells that produce BBK32 on their surface bind to both C1 and C1r and a serum sensitive derivative of B. burgdorferi is protected from killing via the classical pathway in a BBK32-dependent manner. Subsequent biochemical and biophysical approaches localized the anti-complement activity of BBK32 to its globular C-terminal domain. Mechanistic studies reveal that BBK32 acts by entrapping C1 in its zymogen form by binding and inhibiting the C1 subcomponent, C1r, which serves as the initiating serine protease of the classical pathway. To our knowledge this is the first report of a spirochetal protein acting as a direct inhibitor of the classical pathway and is the only example of a biomolecule capable of specifically and noncovalently inhibiting C1/C1r. By identifying a unique mode of complement evasion this study greatly enhances our understanding of how pathogens subvert and potentially manipulate host innate immune systems.
Citation: Garcia, B. L., Zhi, H., Wager, B., Hook, M., & Skare, J. T. (2016). Borrelia burgdorferi BBK32 Inhibits the Classical Pathway by Blocking Activation of the C1 Complement Complex. Plos Pathogens, 12(1), 28. doi:10.1371/journal.ppat.1005404
Keywords: Fibronectin-Binding Protein; Tandem Beta-Zipper; Factor-H-Binding; Regulators C4B-Binding Protein; Experimental Lyme Borreliosis; Staphylococcus-Aureus Fnbpa